Evaluation of Learned Helplessness, Perceived Self-efficacy, and Functional Capacity in Patients With Fibromyalgia and Rheumatoid Arthritis. Issue 2 (March 2019) - Moyano, Sebastián; Scolnik, Marina; Vergara, Facundo; García, María Victoria; Sabelli, Mirtha Rosa; Rosa, Javier Eduardo; Catoggio, Luis José; Soriano, Enrique Roberto
Abstract : Objectives: The aims of this study were to compare learned helplessness (LH) and perceived self-efficacy (SE) in patients with fibromyalgia (FM) and rheumatoid arthritis (RA) and to assess their correlation with functional disability, level of perceived pain, and fatigue. Methods: This multicenter, cross-sectional study included consecutive patients (aged ≥18 years) with RA, according to the 2010 American College of Rheumatology/European League Against Rheumatism criteria, and FM, according to 2010 American College of Rheumatology criteria. Learned helplessness was measured by the Rheumatology Attitude Index, Spanish version; SE with the Arthritis Self-efficacy Scale, Spanish version; functional capacity with the Health Assessment Questionnaire (HAQ), Argentine version; depression with Center for Epidemiological Studies–Depression Scale 7-item version and perceived pain and fatigue by the visual analog scale. Disease activity was measured by the Clinical Disease Activity Index (CDAI) and disease impact with the Fibromyalgia Impact Questionnaire (FIQ). Results: A total of 215 patients, 100 with FM and 115 with RA, were included. Mean age was 59 (SD, 14) years and 58 (SD, 13) years for FM and RA, patients respectively. Whereas LH and depression were significantly higher, SE was significantly lower in FM patients. We found a positive correlation between LH and HAQ, pain, depression, fatigue, FIQ, and CDAI in FM and RA patients. We observed a negative correlation between SE and HAQ, pain, depression, fatigue, FIQ (FM), and CDAI (RA) in both groups. Conclusions: Both LH and SE correlate significantly with functional capacity, perceived pain, disease activity, and disease impact in RA and FM patients. Learned helplessness was higher in patients with active disease or high disease impact, as opposed to those in remission or with low disease impact, and the reverse was true for SE. Patients with FM had significantly more LH, pain, fatigue, and depression and less SE compared with those with RA.